Penerapan Market Basket Analisys Menggunakan Algoritma Apriori Dalam Melihat Perilaku Konsumen - shabrina Anisa Putri; Asep Erik Nugraha (Jurnal Ilmiah Wahana Pendidikan, 2022)
The use of information technology is a necessary for Economics. Not only used during the transactions, information technology also used to collate the data for selling strategies in the future. KOSMI is a sharia cooperative that was established in 2019 and has implemented the use of information technology. Since the covid pandemic apppeard, KOSMI has some problems to promote their goods to the consumers. By using data mining information technology, KOSMI can recommend buyers with items they might be interested in. Before processing the data, this research conduct data mining to filter hundreds of transaction bill to find the interconnected data. The 50 relevan transactions found are then entered into a data mining software, Tanagra 1.4.50 version. Type of data mining methods commonly called Market Basket Analysis is used to see the behavior patterns of consumers. One of the algorithms used is the a priori algorithm. With 5% minimum support and 50% minimum confidence value, data processing generates 6 rules that have a lift ratio>1. This data can be used to recommend item to buyers when placing an order.